Inter-religious marriage between Fragrance Law and Maqasid al-Shari’ah - Somantri, Hanhan; Madriadi, Agus; Frimadi, Yusman; Rasyidah, Dewi Riyanti (FISIP UIN SGD Bandung, 2025)
Surah Al-Māidah (5:5) permits Muslim men to marry women from among the People of the Book (Ahl al-Kitāb). However, Article 40 (c) of the Compilation of Islamic Law (Kompilasi Hukum Islam, the Compilation) in Indonesia explicitly prohibits marriage with both polytheist and Ahl al-Kitāb women. In Indonesia’s positive law, interfaith marriage is not explicitly regulated. Law No. 1 of 1974 on Marriage stipulates in Article 2 (1) that a marriage is valid if it is conducted according to the laws of the respective religions and beliefs of the parties involved. Consequently, interfaith marriages are only considered legally valid if one party converts to the religion of the other. This study aims to analyze interfaith marriage from the perspective of Islamic jurisprudence (fiqh al-munākahāt). It employs a qualitative research method with a descriptive-analytical approach through literature review. The findings indicate that the legal rationale (‘illat al-ḥukm) behind the prohibition of interfaith marriage is based on theological and fundamental religious grounds. The stipulations in the Compilation align with the core objectives of Islamic legal theory (maqāṣid al-sharī‘ah), particularly the objectives of safeguarding religion (ḥifẓ al-dīn) and preserving lineage (ḥifẓ al-nasl). Therefore, the transformation of classical Islamic jurisprudence into the Compilation represents an effort to codify and unify Islamic family law within Indonesia’s national legal framework, taking into account the public interest (maṣlaḥah) and the socio-religious context of Indonesian Muslim society. Contribution: This research elucidates the rationale behind the legal prohibitions and demonstrates how the transformation and unification of classical fiqh into Indonesia’s statutory legal framework reflect considerations of public interest and local Muslim societal context. Thus, the study offers valuable insights into the harmonization of religious jurisprudence and state law in a pluralistic society.